Sertifikasi Amil: Studi Eksploratif Kompetensi Amil untuk Mewujudkan Good Amil Governance di Lembaga Amil Zakat Rizki Jember - Anisah Annuriyah Achmad (Fakultas Ekonomi dan Bisnis, 2026)
The potential for zakat in Indonesia is very large, but this potential has not yet been maximized because zakat management is still lacking and the human resources (HR) who manage zakat, in this case namely amil, are still not really high quality. This is one of the consequences of the lack of amil certification being carried out. In fact, the ratio between certified amyl and the overall amount of amyl is very different. This research aims to outline and describe the application of amil competency and its implications for the realization of the principles of Good Amil Governance (GAG) at the RIZKI Jember Amil Zakat Institution, namely Transparency, Accountability, Responsibility, Independence, Fairness, Shariah Compliance, Service Quality. This research uses a qualitative descriptive method using primary and secondary data, namely through interviews, observation and documentation. The results of the research show that after implementing a comprehensive series of amil certification, it has become a form of strengthening amil competency. As a result, the five aspects of competency, namely Knowledge, Skills, Self Concept, Traits, Motives, in amil have been fulfilled and support the realization of Good Amil Governance (GAG) which is implemented significantly in a series of daily operational activities of amil at the Amil Zakat Institute RIZKI Jember. These results show the implications of having standardized amil certification which has an impact on better and maximum zakat management.
Amil Certification: An Explorative Study Of Amil Competencies To Achieve Good Amil Governance At The Rizki Amil Zakat Institute In Jember
FINALISASI oleh Arif 2026 Mei 19
Keywords: Zakat; Amil; Kompetensi; Good Amil Governance (GAG)